Engaging Transformative Organizational Learning to Promote Employability. Issue 163 (3rd September 2019) - Fabbri, Loretta; Romano, Alessandra
Abstract: The article analyzes the learning paths, organizational devices, and system actions taken within the Teaching & Learning Center research and training facility at the University of Siena.